3-year survival rate in acute lymphoblastic leukemia: comparison of ALL-2006 and ALL-2013 Protocols - Avyandita Meirizkia; Dewi Rosariah Ayu; Raden Muhammad Indra; Dian Puspita Sari (Indonesian Pediatric Society, 2021)
Background With advances in supportive and risk-stratified therapy, the 5-year survival rate of acute lymphoblastic leukemia has reached 85.5%. The ALL-2006 treatment protocol was modified and renamed the ALL-2013 protocol, with dose and duration changes. Objective To compare outcomes of the ALL-2006 and ALL-2013 protocols, with regards to mortality, remission, relapse, and three-year survival rates. Methods This was retrospective cohort study. Subjects were acute lymphoblastic leukemia (ALL) patients treated from 2011 to 2018 in Mohamad Hoesin Hospital, Palembang, South Sumatera. The three-year survival rates, relapse, remission rates and comparison of ALL-2006 and ALL-2013 protocols were analyzed with Kaplan-Meier method. Results Mortality was significantly correlated with age at diagnosis <1 year and >10 years, hyperleukocytosis, and high-risk disease status. Patients aged 1 to 10 years, with leukocyte count <50,000/mm3 and standard-risk status had significantly higher likelihood of achieving remission. Mortality was not significantly different between the ALL-2006 protocol group [70.6%; mean survival 1,182.15 (SD 176.89) days] and the ALL-2013 protocol group [72.1%; mean survival 764.23 (SD 63.49) days]; (P=0.209). Remission was achieved in 39.2% of the ALL-2006 group and 33% of the ALL-2013 group (P>0.05). Relapse was also not significantly different between the two groups (ALL-2006: 29.4% vs. ALL-2013: 17.9%; P>0.05). Probability of death in the ALL-2006 group was 0.3 times lower than in the ALL-2013 group (P<0.05), while that of the high-risk group was 3 times higher. Remission was 2.19 times higher in those with leukocyte <50,000/mm3 compared to those with hyperleukocytosis. In addition, relapse was significantly more likely in high-risk patients (HR 2.96; 95%CI 1.22 to 7.19). Overall, the 3-year survival rate was 33%, with 41.7% in the ALL-2006 group and 30.7% in the ALL-2013 group. Conclusion Three-year survival rate of ALL-2006 protocol is higher than that of ALL-2013 protocol but is not statistically significant. Age at diagnosis <1 year and >10 years, hyperleukocytosis, and high-risk group are significantly correlated with higher mortality and lower remission rates. However, these three factors are not significantly different in terms of relapse.